Modélisation et Cartographie des Risques d’érosion Hydrique du Sol par l’application des SIG, Télédétection et Directives PAP/CAR. Cas du Bassin Versant de Beht, Maroc - Ait Yacine E.; Oudija F.; Nassiri L.; Essahlaoui A. (European Scientific Journal, ESJ, 2019)
Modeling and mapping potential risk of soil erosion is extremely important to watershed management. The advanced technology of geomatics as Geographic Information System (GIS) and Remote sensing (RS) become a valuable source of assistance to estimate soil loss at the large area, in faster manner, and with a consistent level of reliability.The main objective of this work is to elaborate the map of vulnerable area to the hydrical erosion based on the The Priority Actions Programme / Regional Activity Centre (PAP/RAC) method using (GIS) and (RS) in the Beht watershed in upstream of Ouljat Sultan dams. This watershed occupies the upstream part of El Kansera basin and it is one of sub-watersheds of the Sebou River. It extends an area of approximately 2472km2 and overlaps on two geomorphologicals units: the Central Meseta and the Tabular Middle Atlas. En deed, the PAP/RAC method is based on three approaches: the first is the predictive approach that provides a synthetic map of erosive states, the result of this step shows that59% of study basin is subjected to a high and very high degree of erosion. The second is the descriptive approach that allows to maps the various erosion forms. Result of this approach hows that only 21% of study watershed is stable or stabilized by vegetation; the rest is infected by all erosion forms with different degree. The third approach provides a consolidated and integrated map of erosion, which shows that the degree of erosion intensity is proportional to that of the causal factors and especially in the area who combine the causal factors, (slope and friability of soil at their high levels, and the vegetation cover and its density at their low levels).La modélisation et la cartographie des potentiels risques de l’érosion hydrique des sols est d’une grande importance dans la gestion et l’aménagement des bassins versants. Ce travail a pour objectif d’élaborer la carte de vulnérabilité des sols à l’érosion dans le bassin versant de Beht en amont du barrage de Ouljet Soltane, en se basant sur les directives du Programmes d’Actions Prioritaires/ Centre d’Activité Régionale (PAP /CAR).Cette méthode consiste à définir les principaux facteurs causaux (pente, lithologie, érodibilité, occupation du sol, densité du couvert végétal, formes et ampleur d’érosion existant sur terrain) et fait appel à un ensemble de données ( MNT, Géologie, images Landsat 8,et autres..) en utilisant SIG et télédétection. Le bassin versant de Beht, qui est un affluent principal de l’Oued Sebou, couvre deux unités géomorphologiques dont le moyen Atlas et le plateau central. L’application de la méthode PAP/CAR, qui comporte trois phases, a donné les résultats suivants: dans la 1 ère phase (prédictive) la carte des états érosifs, montre que 59% des terrains du bassin d’étude sont exposé à des fortes à très fortes érosions. Les résultats obtenus pour la 2 ème phase (descriptive), montrent que ce bassin versant est réellement touché par l’érosion à différentes formes et que seulement 21% de la surface peut être considérée comme stable ou stabilisée mais avec un risque d’instabilité non nul. Pour la 3 ième phase, qui est celle d’intégration, elle a permis d’obtenir la carte consolidée de l’érosion qui montre que le degré d’intensité de l’érosion est proportionnel à celle des facteurs causaux et surtout dans les zone de combinaison des facteurs (pente et friabilité du sol à leurs haut niveau et le couvert végétal et sa densité à leurs bas niveaux).